Sundanese Family Strength: A Preliminary Study - Sari, Yunita; Afiatin, Tina; Subandi, Subandi; Setiawan, H.W. (Jurnal Ilmiah Peuradeun, 2020)
Various studies related to family strength indicators have been carried out in various countries. However, research on family strength in Asia, especially in Indonesia, which has a variety of cultures is still not widely conducted. The purpose of this study was to properly explore key indicators of Sundanese family strength in Bandung City, West Java, Indonesia. This study used the qualitative approach specifically the phenomenology method. The participants were four Sundanese families in Bandung City, who identify its family members are Sundanese and are confirmed by the surrounding community as Sundanese. Data were analyzed with thematic analysis. The result uncovered five themes: 1) accommodating conflict strategy or “silih narima” 2.) positive communication 3.) the emotional intimacy 4.) knowing (philosophy of life) or “neang elmu” 5.) the social support of the family of origin. The implication of these findings is discussed.